2022
DOI: 10.1080/21655979.2022.2076497
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase affects the sensitivity of esophageal squamous cell carcinoma cells to chemotherapy with cisplatin via the Wnt/beta-catenin signaling pathway

Abstract: Recent studies have shown that the expression of integrin-linked kinase (ILK) was related to the occurrence, development, and malignant progression of esophageal squamous cell carcinoma (ESCC). However, research on the relationship between ILK and the chemosensitivity of ESCC has to date not been reported. The present study found that ILK was highly expressed in ESCC cell lines, and the overexpression of ILK in ESCC cells reduced the incidence of cell apoptosis and alleviated the cytotoxicity on cells induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In fact, some studies have shown that ILK is not only upregulated in a variety of malignancies but is also associated with a poor patient prognosis. At the same time, our research group previously demonstrated that interfering with ILK can significantly inhibit proliferation, invasion, and migration of ESCC cells and also improve patient prognosis [ 17 , 33 ]. ILK, as a therapeutic target, has attracted a lot of research attention.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies have shown that ILK is not only upregulated in a variety of malignancies but is also associated with a poor patient prognosis. At the same time, our research group previously demonstrated that interfering with ILK can significantly inhibit proliferation, invasion, and migration of ESCC cells and also improve patient prognosis [ 17 , 33 ]. ILK, as a therapeutic target, has attracted a lot of research attention.…”
Section: Discussionmentioning
confidence: 99%